Comparative study of a liposome and emulsion system with cinnamon essential oil on the quality and proteolysis of refrigerated minced pork - Wu, Kegang; Zhang, Tong; Chai, Xianghua; Wang, Pingping; Duan, Xuejuan (Frontiers in Nutrition, 2024)
Essential oils have been recognized for their strong antibacterial property, making them an innovative approach for preserving meat. However, their chemical instability and direct impact on meat proteins limit their application. To overcome these limitations, various loading systems have been explored. This study aimed to compare the effect of cinnamon essential oil (CEO) loaded in a liposome and emulsion system on the proteolysis of minced pork and to evaluate the advantages of each delivery system in preventing microorganism-induced quality deterioration of meat. Minced pork treated with CEO-liposomes exhibited lower pH, total volatile basic nitrogen (TVB-N), and total viable count (TVC) values than CEO-emulsions and provided better protection against microorganisms. SDS-polyacrylamide gel electrophoresis (PAGE) analysis confirmed that CEO-liposome was more effective in protecting proteins from degradation. Moreover, CEO-liposome produced lower amount of bitter amino acids and harmful biogenic amines. Antibacterial mechanisms indicated that CEO-liposome exhibited a stronger inhibitory effect against major spoilage bacteria in meat products by increasing cell membrane permeability. The membrane damage was further supported by an increase in conductivity and the leakage of nucleic acids. Compared to the CEO-emulsion system, CEO-liposome emerged as an effective preservative for minced pork. These results provided important theoretical support for using a bioactive compound delivery system to prevent microorganism-induced quality deterioration in meat.